Heat integration analysis of gas to liquid (GTL) process - Mohd Fuad, Che Nordin (2010)
Gas-to-liquid (GTL) process involves the chemical conversion of natural gas (or other gas sources) into synthetic crude that can be upgraded and separated into different useful hydrocarbon fractions including liquid transportation fuels. A leading GTL technology is the Fischer Tropsch process.The objective of this work is to provide a techno-economic analysis of heat intergrated GTL flowsheet.First,a base case GTL flowsheet from published result is modeled using Aspen Hysys to determine the energy flows,performance criteria, and equipment specifications.Next,heat integration studies by Pinch Analysis are performed to address the heating and cooling utilities.After the integration,100% of heating duty requirement can be saved,and the cooling duty requirement can be saved for about 23%.Finally,an economic analysis is undertaken to determine the energy costing of the GTL flowsheet.It shows,RM171.76 MM/year and RM 0.63 MM/year can be saved from heat utility and cooling utiliy respectively. Finally this research has provided a framework for analyzing and improving the performance of FT-GTL plants.The following tasks have been performed,typical GTL process has been synthesized,thermal pinch analysis has been applied to get the optimum heating and cooling utilities and Aspen Hysys have been used in evaluating the performance and cost of the process.The following recommendations are suggested for future work, Strategies to reduce greenhouse gas (GHG) emissions from the GTL plant,address mass exchange network (MEN) and scale up strategies and analysis should be carried out.